STUDY OF DEFECT ON 180 ML HDPE BOTTLES YOGURT PRODUCTS WITH SMC B11 EXTRUSION BLOW MACHINE AT PT X - Tommy Prasetya Kana; Handika Dany Rahmayanti; HM Didik (Politeknik Negeri Media Kreatif, 2021)
The type of plastic packaging that is popular in the community is bottle packaging. The plastic material that is generally used to make plastic bottles is High Density Polyethylene (HDPE). The plastic bottle industry in Indonesia usually uses a blow molding process in its production process, where the blow molding process consists of injection blow molding, extrusion blow molding and stretch blow molding. The SMC B11 machine is one of the extrusion blow molding machines used to produce plastic bottle packaging. In producing workpieces, this machine still produces several products that are not in accordance with company standards, including in terms of production cycle times and product defects. Defects or defects that are often encountered include the appearance of spots, bent parison which causes the bottle to bend (the bottle body is thin one side) and blow pin which causes the thread to not fit.Keywords— Bottle, Plastic, Defect, Extrussion Blow Molding